A Multi-Level Multi-Objective Quadratic Programming Problem with Fuzzy Parameters on Objective Functions - Emam, Usama (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2016)
This paper proposes an algorithm to solve multi-level multi-objective quadratic programming problem with fuzzy parameters in the objective functions, This algorithm uses the tolerance membership function concepts and multi-objective optimization at each level to develop a fuzzy Max-Min decision model for generating satisfactory solution after applying linear ranking method on trapezoidal fuzzy numbers in the objective functions, An illustrative example is included to explain the results.